A NOVEL FOUR-STEP ITERATION SCHEME WITH NUMERICALS - Anjali; Mehra, Seema; Chugh, Renu (Communications in Mathematics and Applications, 2026)
This study presents a four-step iteration method for approximating the fixed points of a contractive-like mapping. We also consider the strong convergence, order of convergence and stability of the proposed method. Moreover, we present some numerical illustrations to validate our method and these numerical illustrations have been compared with some similar schemes available in the literature.